Histological Appearance of Distal Second Part of Duodenum with Normal Endoscopic Findings in Bangladeshi People in a Tertiary Care Hospital - Karim, Mohammad Enamul; Huda, Mohammad Mahmudul; Masud, Hasan; Biswas, Prodip Kumar; Rana, Mushtaque Ahmed; Vhadury, Suvash Chandra; Haque, Mohammad Ahsanul; Ahmed, Dewan Saifuddin (Journal of Medicine, 2015)
Biopsy from the distal second part of duodenum is now widely accepted as a useful and simple way to evaluate patients with malabsorption or other small intestinal diseases.Histological findings of the second part of duodenum in tropical countries are different from that of other countries. Histological appearance of the second part of the duodenum may be changed due toceliac disease, tropical sprue, tropical enteropathy and some other conditions. As Bangladeshi people, we are exposed to different infection always due to its geographical distribution. Normal histological appearance of second part of duodenume.g. standard villous architecture, length, villous crypt ratio, IELcounts of our country in not known. The main objective of our study was to see the normal histological appearance of second part of duodenum in our country so that we can differentiate from abnormal condition. This observational study was carried out in the Department of Gastroenterology & Pathology, Bangabandhu Sheikh Mujib Medical University, (BSMMU)during the period of July 2010 to June 2011. A total of 116 patients were included from out patientdepartment and admitted patient in the department of Gastroenterology during the study period. Among the total numbers, the mean age was 32.7±9.77 (±SD) years.In our study, 48.27% subjects had finger shaped villous with normal height, 27.58% had both normal and broad villous, 22.41% subjects showed mixed findings of normal, broad and blunted villous and only 1.7% subjects showed broad and blunted villous without normal architecture. In our study, the highest IEL count was 62 cells per 100 epithelial cells and lowest value was 16. Mean value IEL/100 cells were 32.52 ±8.63 (±SD) and 95%CI was 1.57. The result of the study was very similar to Asian people but a little different from the western population. DOI: http://dx.doi.org/10.3329/jom.v16i1.22385 J MEDICINE 2015; 16 : 23-26